Active power control algorithm for distributed photovoltaic power generation cluster based on operating efficiency of photovoltaic power generation unit. Issue 13 (14th December 2017) - Bi, Rui; Liu, Xianfang
Abstract : In order to solve the active power control problem of the distributed photovoltaic (PV) power generation cluster, power control system based on hybrid structure multi‐agent system is adopted. By simulating the movement of a single ant using ant colony algorithm to solve the traveling salesman problem problem, an active power algorithm based on the improved ant colony algorithm is proposed. The power completion rate index based on operating efficiency of PV power generation unit is defined and used to update the pheromone in the improved ant colony algorithm. Finally, an example of distributed PV power generation unit including ten distributed generation units is used to simulate the control effect of the proposed algorithm. Finally, an example of distributed PV power generation unit including ten distributed generation units is used to simulate the control effect of the proposed algorithm. The results show that the algorithm not only introduces the real‐time operation information of the PV unit but also achieves the different control objectives by selecting the control parameters of the algorithm.